In ecclesiae redintegranda unitate: re Teoderico e la fine dello Scisma Acaciano = In ecclesiae redintegranda unitate$bKing Theoderic and the end of the Acacian Schism - Cristini, Marco (Rivista di storia della Chiesa in Italia, 2019)
The negotiations which led to the end of the Acacian Schism involved pope Hormisdas, emperor Anastasius I and his successor Justin I. Our main source, namely the Collectio Avellana, is almost entirely silent about king Theoderic, whose role has until now been regarded as minor. A careful examination of the embassies sent to and from Constantinople between 515 and 519, however, indicates that the Gothic sovereign influenced the negotiations in the hope of obtaining the imperial recognition for his would-be heir, Eutharic, who became consul together with emperor Justin a few months before the re-establishment of the Church’s unity.